2010
DOI: 10.1021/bm101033g
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of the Interaction between siRNA and PAMAM G7 Dendrimers by SAXS, ITC, and Molecular Dynamics Simulations

Abstract: A prerequisite for the use of dendrimers as drug delivery vehicles is the detailed molecular understanding of the drug interaction. The purpose of this study was to characterize the self-assembly process between siRNA and generation 7 poly(amidoamine) dendrimers and the resulting dendriplexes in aqueous solution using structural and calorimetric methods combined with molecular dynamics simulations. Complexes with a length scale of 150 nm showed a decreasing size with increasing amine-to-phosphate ratio by dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
55
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 77 publications
8
55
0
Order By: Relevance
“…Hence the PEG-3350 complexes contain in average one tRNA molecules, the anthracene complexes five molecules and the PEG-6000 complexes ten molecules ( Figure 1-panel A). The tRNA aggregation and particle formation in the presence of PEG and mPEG-anthracene were very similar to those of PEG-DNA complexes recently reported [21,22]. Similarly in the cases of dendrimers and PEGylated dendrimers, the mica surface was covered by a layer that attributed to a mixture of free dendrimer, free pegylated dendrimers and free tRNA ( Figure 1-panel B).…”
Section: Afm Images and Morphology Of Synthetic Polymertrna Complexessupporting
confidence: 83%
See 1 more Smart Citation
“…Hence the PEG-3350 complexes contain in average one tRNA molecules, the anthracene complexes five molecules and the PEG-6000 complexes ten molecules ( Figure 1-panel A). The tRNA aggregation and particle formation in the presence of PEG and mPEG-anthracene were very similar to those of PEG-DNA complexes recently reported [21,22]. Similarly in the cases of dendrimers and PEGylated dendrimers, the mica surface was covered by a layer that attributed to a mixture of free dendrimer, free pegylated dendrimers and free tRNA ( Figure 1-panel B).…”
Section: Afm Images and Morphology Of Synthetic Polymertrna Complexessupporting
confidence: 83%
“…It has been shown that synthetic polymers induce significant changes in DNA and RNA solubility and structure under given conditions [8][9][10][11][12][13][14][15][16][17][18][19][20]. Synthetic polymers are also used to transport miRNA and siRNA in vitro [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. PEGylation of synthetic polymers such as dendrimers is shown to reduce toxicity and increase biocompatibility and DNA Transfection [6,7,9].…”
Section: Introductionmentioning
confidence: 99%
“…The four metastates (m1-m4) witnessed in the single Anton trajectory have chemical shifts similar to those of the ground state, maintain the F helix as a 3 10 helix separate from the G helix, and position F114 just outside of the buried cavity despite fluctuation in cavity volume and changes in F114-V103 internal distances throughout these metastates (Fig. 1).…”
Section: Defining the Metastates And Intermediate State In The Anton mentioning
confidence: 89%
“…Long-timescale molecular dynamics (MD) simulations now make it possible to witness atomic motions on the nanosecond to microsecond timescale, with a suitable level of agreement with experiment (8)(9)(10)(11). Additionally, with recent advances in specialized computational architectures like Anton, simulation timescales on the order of microseconds to milliseconds in a single trajectory are within reach (7,(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…The binding strength between dendrimer-guest complexes has been determined by isothermal titration calorimetry(ITC) [26][27][28][29], high performance liquid chromatography (HPLC) [30] and fluorescence spectroscopy [31][32][33]. Detailed conformations of dendrimers interacting with guest molecules have been studied by nuclear magnetic resonance(NMR) [34][35][36] and the size of the dendrimer-guest complexes has been measured by dynamic light scattering (DLS) [22,31].…”
Section: Introductionmentioning
confidence: 99%